Studying the Distribution of Hospitalization Services at Hospitals in East Azerbaijan Province - Ali Janati; Ali Imani; Hassan Almaspoor Khangah (Tehran University of Medical Sciences, 2017)
Background and Aim: It is necessary that various aspects of health information and statistics are identified and measured since health problems are getting more complex day by day. This study is aimed to investigate the distribution of Hospitalization Services in Hospitals in East Azerbaijan province. Materials and Methods: This research was a descriptive, cross-sectional study, which aimed to determine the share of hospitalization services in different sectors providing healthcare services in East Azerbaijan Province. The study population consisted of all health service providers, including the public sector, private, charity, military, Social Security and NGOs in the province of Eastern Azerbaijan. The data from all functional health sectors, including health centers and hospitals were studied during 2014. The data relevant to performance were collected according to a pre-determined format (researcher-built checklist). Content validity of checklist was approved by five Health Services Management professionals and experts.  Results: The study findings showed that the maximum and minimum number of surgeries has been done in the public sector (63.1%) and the non-governmental sectors (3%), respectively. The public sector (71.9%) and non-governmental sectors (Red Crescent and Azad University) (1.2%) provided the maximum and minimum hospitalization services, respectively.  Conclusion: According to the study findings, Policies should be aimed to create balance and harmony in the provision of services among all service providers.